The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
PJMHS 2022
DOI: 10.53350/pjmhs20221612527
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Role of Lactulose on Hepatic Encephalopathy Among Cirrhotic Patients with Acute Upper Gastrointestinal Bleeding

Abstract: Aim: To determine the efficacy of lactulose as prophylaxis on hepatic encephalopathy among cirrhotic patients of acute upper gastrointestinal bleeding. Material and methods: We carried out this randomized control trial in multi centers including Mian Rashid Hussain Shaheed Memorial Hospital Pabbi Nowshera. KPK and Isra University Hospital, Hyderabad from February 2022 to July 2022 (06 months) with total no of 80 patients. Group A patients received lactulose while group B patients received sweet syrup placebo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Overall, our review yielded five randomized trials that evaluated the effect of lactulose for the prevention of overt HE in the setting of AUGIB. All the trials [6][7][8][9] except for one [2] reported a significantly lower incidence of precipitated HE, translating into a RR of 0.38 (0.23-0.62). For the outlier study by Rattanasupar et al [2] it is important to note that the study protocol allowed for the use of an additional rescue laxative with lactulose in cases of inadequate bowel movement, which might have influenced the results.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Overall, our review yielded five randomized trials that evaluated the effect of lactulose for the prevention of overt HE in the setting of AUGIB. All the trials [6][7][8][9] except for one [2] reported a significantly lower incidence of precipitated HE, translating into a RR of 0.38 (0.23-0.62). For the outlier study by Rattanasupar et al [2] it is important to note that the study protocol allowed for the use of an additional rescue laxative with lactulose in cases of inadequate bowel movement, which might have influenced the results.…”
Section: Discussionmentioning
confidence: 96%
“…Manual searching of reference lists of the included studies was also undertaken to ensure that no potentially relevant items were overlooked. The study methodology was designed and executed to adhere to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines [8].…”
Section: Information Sources and Search Strategymentioning
confidence: 99%
See 3 more Smart Citations